﻿Evaluation of the permissible 99Mo activity in the KL-15 cask in the design of transportation and process scheme - Vladimir V. Fomichev; Denis A. Pakholik; Oleg Yu. Kochnov; Nikita V. Kuznetsov; Mikhail V. Kharitonov; Vyacheslav V. Nichugovsky (Nuclear Energy and Technology, 2022)
The demand for the use of radioactive isotopes in medicine is increasing with each coming year necessitating the increased output of radionuclide products. One of the most widely spread radionuclides used in medicine is technetium-99m (99mТс) (Feasibility of producing molybdenum-99 2015, NEA 2012, The Supply of Medical Radioisotopes 2015). The very short 99mТс life (6-hour half-life) requires its production directly on the site of medical treatment. This is achieved using molybdenum-technetium generators (Kodina and Krasikova 2014, Technical Reports No. NF-T-5.4. 2013, Technetium-99 Generator 2021) loaded with molybdenum-99 (99Мо), which uninterruptedly decays (half-life of 66 hours) yielding 99mTc. Close attention must be paid in the course of production of molybdenum-technetium generators to radiation safety during transportation of 99Мо on the territory of the manufacturing facility. The main measure for ensuring radiation safety during transportation of 99Мо is the application of special packaging kits. The Karpov Institute of Physical Chemistry JSC uses a wide range of packaging kits of types A and B for transportation of radioactive materials on the territory of the manufacturer with design features providing the required level of radiation safety. In particular, the KL-15 shipping cask loaded/unloaded from the top is used for onsite transportation of 99Мо for charging molybdenum-technetium generators. The maximum permissible activity of 99Мо is not specified in the passport of the KL-15 cask. Planned construction of a radionuclide production shop in accordance with GMP requirements will require the increase of output of target radionuclides by several times. The above considerations necessitated the evaluation of the maximum permissible activity of 99Мо planned to be transported in KL-15 casks. No other type of standard casks can be used because of their outside dimensions prohibiting the unloading of 99Мо inside the “hot” chamber. Calculation and experimental evaluation of permissible 99Мо activity during transportation inside the KL-15 cask was performed. The paper presents the calculated evaluation of the maximum permissible activity of 99Мо in a KL-15 cask to ensure the radiation exposure of personnel of group A working with the cask not exceeding the established level at the enterprise (80 μSv per shift) and not requiring the use of additional measures and means of protection. The results of the work allow us drawing the conclusion that the KL-15 cask ensures the required level of radiation safety with up to 241 Ki of 99Мо loaded in the cask.